Classroom management styles and their relationship to motivation to learn among secondary school students: A field study on a sample of first-year secondary school students - Abbassa, Amina; Djarane, Amina (Journal of Social Sciences and Humanities, 2025)
The primary objective of the present investigation was to elucidate the patterns of classroom management and their association with the motivation for learning among first-year secondary school pupils. The participant cohort comprised (57) students during the academic year (2023). For the execution of the study, a questionnaire was employed as the instrument to evaluate classroom management styles alongside motivation for learning. Additionally, frequencies, percentages, arithmetic mean, and standard deviation were utilized to ascertain the characteristics of the sample and to formulate the research hypotheses, leading to the following findings: A significant correlation exists between classroom management styles and motivation for learning. The authoritarian classroom management style is predominantly utilized by secondary school educators. Furthermore, no discernible differences were observed among first-year secondary school students in terms of motivation to learn attributable to the gender variable.